2017
DOI: 10.1039/c7lc00053g
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of silver nanoparticles by DHA-treated cancer cells examined by surface-enhanced Raman spectroscopy in a microfluidic chip

Abstract: This paper reports on the synthesis and application of biocompatible and sensitive SERS nanoparticles for the study of uptake of nanoparticles into living cells in a microfluidic chip through surface-enhanced Raman spectroscopy (SERS). The nanoparticles were fabricated as beta-cyclodextrin-coated silver nanoparticles (Ag@CD NPs) modified with para-aminothiophenol (p-ATP) and folic acid (FA) on the surface. The p-ATP molecules act as the Raman reporter while the FA tags have high affinity for folate receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In addition, the AEFs for the other main peaks were calculated and listed in Table S3 in the Supporting Information, which showed that all AEFs were higher than 10 8 . It should be noted that this value is among the highest ever obtained, since reported values typically range from 10 6 to 10 8 (Table S4, Supporting Information) …”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, the AEFs for the other main peaks were calculated and listed in Table S3 in the Supporting Information, which showed that all AEFs were higher than 10 8 . It should be noted that this value is among the highest ever obtained, since reported values typically range from 10 6 to 10 8 (Table S4, Supporting Information) …”
Section: Resultsmentioning
confidence: 73%
“…Integrating this Ag‐ZnO nanostructure into a microfluidic system permitted the analysis of glucose solutions with various concentrations . In addition, other materials, such as Ag@ZnO, beta‐cyclodextrin‐coated Ag nanoparticles, and certain semiconductor nanoparticles, have been successfully integrated into microfluidic chips, and these novel materials have exhibited outstanding SERS sensing performance.…”
Section: Introductionmentioning
confidence: 99%
“…TfR might be upregulated in order to mediate endocytosis of transferrin loaded with increased concentrations of iron. (17,18) We found that DHA decreased TfR mRNA expression and this knockdown of TfR further enhanced the cytotoxic activity of DHA. Most cancer cells have greater numbers of iron-attracting TfR on their cell surface when compared to normal cells.…”
Section: Discussionmentioning
confidence: 76%
“…Increased autophagic activity results in rapid degradation of p62, whereas a lack of autophagy leads to accumulation of p62. (17) In the present study, we explored the impact of DHA treatment on cell proliferation, apoptosis and autophagy in endometrial and cervical cancer cells. Our results would provide further evidence supporting DHA as a possible anticancer drug for the treatment of endometrial carcinoma and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of microfluidic devices coupled with Raman spectroscopy have been successfully used for sample preconcentration or storing cells during the spectroscopic analysis [22][23][24].…”
Section: Advances In Condensed Matter Physicsmentioning
confidence: 99%